Identification of mitochondria-related genes associated with anesthetics in patients undergoing off-pump coronary artery bypass grafting surgery - Zhang, Yuhu; Li, Xinjian; Sun, Tingru (Frontiers in Surgery, 2025)
BackgroundAnesthetics have been reported to play a protective role in the heart during surgery. This study aimed to identify mitochondrial-related genes (Mito-RGs) involved in sevoflurane- and propofol-induced anesthesia in patients undergoing off-pump coronary artery bypass grafting (OPCABG) surgery.MethodsThe GSE4386 dataset, which contains atrial samples obtained from patients receiving sevoflurane or propofol during OPCABG, was downloaded from GEO database for differential expression analysis and immune cell infiltration analysis between the pre-operative and post-surgery groups. Furthermore, to model the ischemia-reperfusion injury encountered during cardiac surgery, we established an in vitro hypoxia/reoxygenation (H/R) model and investigated the effects of sevoflurane and propofol on the expression of hub genes in cardiomyocytes subjected to H/R injury.ResultsIn this study, we identified a total of 11 common Mito-RGs that were influenced by sevoflurane and propofol during OPCABG. Furthermore, a PPI network of these genes was constructed using STRING, followed by the application of the MCODE and cytoHubba plug-ins to further identify hub genes within the network. Our analysis revealed that MCL1, RGS2, PPP1R15A, and MAFF may be the hub Mito-RGs associated with anesthetics. In the post-surgery group, the levels of these genes were negatively correlated with pro-inflammatory M1 macrophages. Notably, compared to pre-OPCABG levels, both sevoflurane and propofol significantly upregulated the expressions of these four hub genes in atrial samples following OPCABG. Furthermore, RT-qPCR and western blot analyses validated that both sevoflurane and propofol can upregulate the expression of Maff, Ppp1r15a, Rgs2, and Mcl1 in H9C2 cardiomyocytes following H/R injury.ConclusionCollectively, these four genes may be linked to the potential cardioprotective effects of anesthetics during OPCABG, which could facilitate further research into the underlying mechanisms and contribute to the development of a more comprehensive and effective anesthesia protocol.